2008
DOI: 10.1016/s0027-9684(15)31294-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Epidemiology in Blacks and Whites: Disparities in Incidence, Mortality, Survival Rates and Histology

Abstract: Background-This study presents black-white breast cancer statistics, tumor histology and receptor status, and treatment patterns for all ages and by age groups (under 40, between ages 40 and 49, and age 50 and over).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(180 citation statements)
references
References 41 publications
13
159
2
6
Order By: Relevance
“…Metzeger et al showed that, from biological point of view, the age of 8 year-old dogs is equal to that of 48-51 years in humans (Metzger et al, 2005;Queiroga et al, 2011). Investigations have demonstrated that the peak incidence of CMGTs occurs in dogs aged approximately 7-10 years, which is equal to 44-56 years in humans and is roughly equal to the peak of HBC incidence (Jamal et al, 2007;Baquet et al, 2008). In terms of the involved anatomic region as well as the histopathological results, this study was in line with other similar studies (Karyannopoulo et al, 2005;Andrade et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Metzeger et al showed that, from biological point of view, the age of 8 year-old dogs is equal to that of 48-51 years in humans (Metzger et al, 2005;Queiroga et al, 2011). Investigations have demonstrated that the peak incidence of CMGTs occurs in dogs aged approximately 7-10 years, which is equal to 44-56 years in humans and is roughly equal to the peak of HBC incidence (Jamal et al, 2007;Baquet et al, 2008). In terms of the involved anatomic region as well as the histopathological results, this study was in line with other similar studies (Karyannopoulo et al, 2005;Andrade et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Ageadjusted mortality for blacks, although showing a declining trend, was nearly twice that of whites (7.79 vs 3.96, P < 0.05). Squamous cell carcinoma was more commonly diagnosed in blacks and white females, whereas adenocarcinoma was more common among white males (P < 0.001) [41] . The reasons are economic status, diet, and poor eating habits etc.…”
Section: Incidencementioning
confidence: 96%
“…Racial disparity also occurs between the 2 types of esophageal cancer. ESCC is more prevalent among Blacks, whereas EAC is at least twice as common in Whites as compared with other ethnic groups (7,8). Once diagnosed, Black patients showed poorer overall survival than Whites (9,10).…”
Section: Introductionmentioning
confidence: 95%